1996
DOI: 10.1021/ja9616084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Inositol Phosphodiesters by Phospholipase C-Catalyzed Transesterification

Abstract: Transesterification of primary alcohols with inositol 1,2-cyclic phosphate (IcP) in the presence of phosphatidylinositol-specific phospholipase C (PI-PLC) resulted in the formation of O-alkyl inositol 1-phosphates. The starting IcP was obtained in a single step by PI-PLC catalyzed cleavage of phosphatidylinositol from the soybean phospholipid. The transesterification reaction was performed with a series of 20 structurally diverse hydroxyl compounds, ranging in the structural complexity from methanol to the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…The degree of alcohol deprotonation in the reverse reaction (which should be the same as the degree of protonation in the forward reaction) should depend on the alcohol pK a and the strength of the enzymic base. The externally added alcohol undergoes an exchange with an alcohol of a ternary complex of the products ( Figure 9) and uses the binding site formerly occupied by the leaving group alkoxide (10). The WT PI-PLC showed a small Brønsted coefficient of nuc ) -0.10 ( 0.02, somewhat lower than that obtained for reactions of RNase A with phenyl esters of uridine 3′-phosphate (-0.17 ( 0.03; 53).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The degree of alcohol deprotonation in the reverse reaction (which should be the same as the degree of protonation in the forward reaction) should depend on the alcohol pK a and the strength of the enzymic base. The externally added alcohol undergoes an exchange with an alcohol of a ternary complex of the products ( Figure 9) and uses the binding site formerly occupied by the leaving group alkoxide (10). The WT PI-PLC showed a small Brønsted coefficient of nuc ) -0.10 ( 0.02, somewhat lower than that obtained for reactions of RNase A with phenyl esters of uridine 3′-phosphate (-0.17 ( 0.03; 53).…”
Section: Discussionmentioning
confidence: 91%
“…Conversion of PI to IcP is 100-1000-fold faster than hydrolysis of IcP to IP depending on the conditions used (8,9). On the basis of the stereochemical course of the reaction and the X-ray structure of PI-PLC complex with myo-inositol, a mechanism involving general base-general acid catalysis, reminiscent of that of ribonuclease A, has been proposed for both steps (8,(10)(11)(12)(13) as …”
mentioning
confidence: 99%
“…The PI cleavage of bacterial PI-PLC constitutes an intramolecular phosphotransferase step that cleaves PI to inositol-1,2-cyclic phosphate and a cyclic phosphodiesterase step that converts inositol-1,2-cyclic phosphate to inositol-1-phosphate (62). Bruzik et al (57) reported the first enzymatic synthesis of inositol phosphodiesters starting from alcohols and inexpensive, readily available soybean phospholipids. The PI-PLC reactions were also successfully applied to the preparation of a number of complex inositol phosphoesters of mono-and oligosaccharides, nucleosides, and peptides.…”
Section: Plcmentioning
confidence: 99%
“…PLC which hydrolyses phosphatidyl inositol (PLC PI ) [EC 3.1.4.10] can also be obtained from B. cereus and B. thuringiensis [92]. Application in the production of inositol phosphates has recently been reported [93].…”
Section: Enzyme Source For Biocatalysismentioning
confidence: 99%
“…Interestingly, it has recently been observed that Ca 2+ dependence in cabbage PLD is pH dependent [99]. In a recent work Bruzik et al [93] compare the mechanism of different phosphoesterases and their tendency to catalyze efficiently the transesterification reaction by dividing them into three groups (Scheme 4).…”
Section: Scheme 3 Pld Catalyzed Polar Head Exchange Gives a New Phosmentioning
confidence: 99%